The Wako Cohort Study: Design and Profile of Participants at Baseline - Yuri Yokoyama; Yu Nofuji; Takumi Abe; Kumiko Nonaka; Yumi Ozone; Yuka Nakamura; Shiina Chiaki; Takumi Suda; Naoko Saito; Mai Takase; Hidenori Amano; Susumu Ogawa; et al. (Journal of Epidemiology)
Background: We launched the Wako Cohort Study in 2023 to identify individual and socio-environmental factors related to the extension of healthy life expectancy and the reduction of health disparities among community-dwelling adults and to develop health promotion and care prevention strategies. This study profile aims to describe the study design and participants’ profile at baseline. Methods: The Wako Cohort Study is a prospective study of community-dwelling adults aged ≥40 years living in Wako City, Saitama Prefecture, Japan. The Wako Cohort Study consists of two surveys: a mail-in survey for persons aged ≥40 years and a face-to-face assessment (on-site survey) for those aged ≥65 years. The survey items were designed considering the following points: 1) life course perspective (transition from middle to old age in the life course), 2) health indifference, and 3) employment in older age. Results: A total of 8,824 individuals participated in the mail-in survey (2,395 persons aged 40–64 years and 6,429 aged ≥65 years). Of those aged ≥65 years who returned the mail survey, 1,004 participated in the subsequent on-site survey. Men aged ≥65 years tended to have higher health interests than those aged 40–64 years; however, this was not true for women. In the mail-in survey, 30.4% of those aged ≥65 years were employed. Conclusion: The Wako Cohort Study is expected to provide new insights into the development of strategies to extend healthy life expectancy and reduce health disparities in Japan.